Zinc Supplementation against Eimeria acervulina-Induced Oxidative Damage in Broiler Chickens - Nedyalka V. Georgieva; Margarita Gabrashanska; Ventsislav Koinarski; Zvezdelina Yaneva (Veterinary Medicine International)
This study was undertaken to determine the dietary supplements of Zn containing diet on the antioxidant status in chickens experimentally infected with Eimeria acervulina. The antioxidant status was monitored via determination of MDA concentrations and erythrocyte SOD and CAT activities, as well as vitamin E, vitamin C, Cu, and Zn in liver, muscle, and serum. The results showed increased MDA (𝑃<.05), CAT (𝑃<.001), and decreased SOD (𝑃<.001) in the infected birds. Significant changes in Cu and Zn concentrations and dramatically reduction of vitamin C and E concentrations in the infected chickens were found. The observed deviations in the studied enzymes and nonenzymatic parameters evidence the occurrence of oxidative stress following the infection and impaired antioxidant status of chickens, infected with Eimeria acervulina. Our results proved the ameliorating role of CuZn(OH)3Cl (0.170 g per kg food) against Eimeria acervulina-induced oxidative damage in infected chickens.